In situ measurement of gold nanoparticle production - Affandi, Mohd. Syafiq (SPIE, 2015)
The closeness of the experimental and theoretical values enables the development of an in situ characterization technique to monitor and analyze the production of gold nanoparticles (NPs), overcoming the use of high-end and expensive instrumentation. Gold NPs below the radius size of 10 nm were successfully synthesized in accordance with a few working parameters of pulse laser ablation in a liquid technique. In this report, the size, shape, concentration, and aggregation properties of gold NPs were estimated by the Mie-Gans model based on a reliable and interactive real-time absorption spectroscopy. The major features can be an important means toward determination of efficient process measures, productivity of gold NPs generated, and efficiency of the mass ablation rate. The accuracy in the measurement is confirmed via transmission electron microscopy analysis.